1995
DOI: 10.1007/bf02940703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dampness on the enteric bacilli, SIgA and pathological studies in rats

Abstract: Thirty rats were divided into three groups: Damp group (relative humidity was over 90% and temperature 18--25*C ), Cold group (T: 2 -+ 2"(2, RH: 54 -+ 4 % ) and normal control group ( T: 18--25"(2, RH: 54-+ 4%). The resu!t.s showed that number of Escherichia coli increased greatly while number of bifidobacterium reduced in high moisture. In Damp group, level of secretory IgA was much higher as compared with that of the normal controlled and Cold group. Th/i and Ts/c in Cold group and in Damp group were slightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…As the crucial immunoglobulin on the small intestinal mucosa, sIgA is the first line of defense on the intestinal mucosa and has resistance to multiple endogenous commensal bacteria and foreign invading pathogens. Previous research has shown that cold can reduce the concentration of sIgA in the gut [ 40 ]. We reached a similar result that chronic cold stress resulted in a decline in sIgA concentrations in the jejunal mucosa of Yorkshire pigs.…”
Section: Discussionmentioning
confidence: 99%
“…As the crucial immunoglobulin on the small intestinal mucosa, sIgA is the first line of defense on the intestinal mucosa and has resistance to multiple endogenous commensal bacteria and foreign invading pathogens. Previous research has shown that cold can reduce the concentration of sIgA in the gut [ 40 ]. We reached a similar result that chronic cold stress resulted in a decline in sIgA concentrations in the jejunal mucosa of Yorkshire pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, traditional Chinese medicine states that “the kidney governs the bone,” so in the prognosis and treatment of RA combined with OP, taking into account the protection of the kidney is also the key to preventing and treating the symptoms of osteoporosis. Zeng Hongbing et al ( 26 ) found that Tripterygium hypoglaucum Hutch may reduce proteinuria and delay kidney injury by reducing the expression of transforming growth factor, inhibiting the proliferation of mesangial mesangium. Wu Xiabo et al ( 27 ) found that the therapeutic effect of Malus Kunmingshan on nephrotoxic nephritis in rats was achieved by reducing urinary protein content, serum urea nitrogen, triglyceride, and total cholesterol, increasing serum albumin and total protein, improving renal function and pathological changes of glomerulus.…”
Section: Treatment Of Ra With Op By Tcm Monomersmentioning
confidence: 99%